2022
DOI: 10.1111/dth.15395
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled, split‐face study of botulinum toxin and broadband light for the treatment of erythematotelangiectatic rosacea

Abstract: To study the efficacy and safety of botulinum toxin (BTX) combined with broadband light (BBL) in the treatment of rosacea‐related erythema and flushing. A randomized, single‐blind, split‐face controlled study including 22 patients with erythemato telangiectatic rosacea were enrolled. Both cheeks were randomly divided into experimental group and control group. They were treated three times with an interval of 1 month. In the first treatment, the experimental group received BBL treatment and intradermal injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 19 publications
0
38
0
1
Order By: Relevance
“…In a recent randomized clinical trial, 22 patients with erythematotelangiectatic rosacea were randomized to be treated with three sessions of injectable BoNT‐A or saline solution. After the last injection treatment, the global flushing, VISIA red value, erythema index, skin physiological indexes, and skin hydration improved, with results maintained for 3 months 24 . Another alternative is the off‐label use of beta‐blockers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent randomized clinical trial, 22 patients with erythematotelangiectatic rosacea were randomized to be treated with three sessions of injectable BoNT‐A or saline solution. After the last injection treatment, the global flushing, VISIA red value, erythema index, skin physiological indexes, and skin hydration improved, with results maintained for 3 months 24 . Another alternative is the off‐label use of beta‐blockers.…”
Section: Discussionmentioning
confidence: 99%
“…Injectable BoNT‐A has been shown to inhibit vasodilator neuropeptides and vasoactive intestinal peptides, decreasing mast cell count and cathelicidin LL‐37‐induced skin erythema which could also downregulate matrix metalloproteinases, which are mechanisms involved in the pathogenesis of rosacea. Small sample size studies 24,34 have shown a reduction in erythema and an improvement in patient satisfaction in the short and medium term after BoNT‐A injections, however, few studies have assessed patients over the long term. In a recent randomized clinical trial, 22 patients with erythematotelangiectatic rosacea were randomized to be treated with three sessions of injectable BoNT‐A or saline solution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Tong et al [ 30 ] tried to assess the efficacy and safety of BoNT combined with broadband light (BBL) in the treatment of rosacea-related erythema and flushing. The authors enrolled 22 subjects with erythematotelangiectatic rosacea.…”
Section: Role Of Bont In Dermatologymentioning
confidence: 99%